PENGEMBANGAN RUANG TERBUKA HIJAU MELALUI PEMANFAATAN ENERGI RAMAH LINGKUNGAN DI KOTA PONTIANAK - -, Kristiani; Lina, Ratu; Arviadifa, Khelista; Kristi, Magdalena Lara (Jurnal Ilmiah Publika, 2023)
Green city development is an approach used to improve environmental quality and reduce adverse impacts in cities around the world. One of the steps that can be taken to achieve the smooth development of green cities is the use of environmentally friendly energy. In this context, the city of Pontianak has undergone significant changes in increasing the use of renewable and environmentally friendly energy. This article details these obstacles, including inadequate infrastructure, policies that need to be adjusted, and public awareness of environmentally friendly practices. In addition, the study explores innovative strategies in the use of renewable energy sources and green technologies to improve the sustainability of cities. With a green city development approach through the use of environmentally friendly energy, Pontianak city strives to create a safer, cleaner, and environmentally friendly environment for future generations. By understanding and overcoming these challenges, it is hoped that it can encourage the development of a sustainable and environmentally friendly city in Pontianak.